Malay building design reflecting the importance of women in the Malay manuscript - Jaffar, Siti Rabiatul Adawiah; Sujud, Arba'ie; Noor Muhammad, Salmah Jan; Kamarudin, Kamariah; Abdul Rahman, Nadiatul Shakinah (Human Resource Management Academic Research Society, 2018)
The design of Malay buildings that are built in diverse forms, based on three main paragraphs, which are the roof, walls and pillars are to fulfill various interests, in line with the community's lifestyle. For the Malay community, Islam has a great influence in the forming of a lifestyle, which then becomes the guide and practice of the audience. Similarly, Malay building designs, featuring designs that is related to the Islamic lifestyle. Islamic values the women’s rights, as the teachings place women in a high and noble position. It is also emphasized on the creation of Malay building designs, while indirectly acknowledging the importance of women in domestic institutions. In fact, this can be examined through the Malay manuscripts, as the main source of references in examining the Malay architectural buildings and design of. Therefore, this article examines the selected Malay manuscripts in order to present the design of Malay architectural buildings, which portrays Muslim woman’s lifestyle through Malik Bennabi’s Cultural Theory.